The Roles and Use of Art as Technology - Adeyanju, J. O. (2014)
Artists do struggle to appeal to their audience by using the medium that best suits them. This they do in order to be fully understood. The architect designs buildings for the utilitarian purpose it serves for the human race. Man needs security from very harsh weather as well as comfort in order to live. The painter represents the socio-cultural changes of his society using paint and brush. So also does the composer of music draw on his consciousness, creating pleasing sounds. The poet chooses his words deliberately in order to communicate. Evidently, what artists intend doing at all time is to express their desire to please.